Education system and exposure to stress and the sense of satisfaction of nursing students - Lewandowska, Anna; Lewandowski, Tomasz; Laskowska, Barbara (Journal of Education, Health and Sport, 2018)
Introduction: The phenomenon of occupational stress can very often be found during the education process among nursing students. A very large number of hours of practical training, contact with the real treatment environment, constitute the same threats as in the case of people already in the profession. Stress, which can have a chronic dimension, poses a risk of dissatisfaction with the decision made and medical mistakes made by students. Satisfaction with the decision made about the profession is a multidimensional factor, including psychosocial values related to work. Objective: The aim of the study is to assess the level of stress among nursing students during the practical education process and to analyze the level of satisfaction with the professional choice made. Material and method: The study covered 200 people who are nursing students graduating from the three-year education period. The selection of respondents was random. The study group consisted of 100% women aged 23-45, living in urban areas (48%) and rural (52%). Research method: The research method used in the work was a diagnostic survey. The research tool used is a self-help questionnaire. Results: The nursing education by the respondents was caused by the need to help others (46%), was a matter of chance (25%), a continuation of family traditions (3%), and the possibility of constant contact with people (8%). Over half of the respondents (56%) are satisfied with the decision made. The respondents feel needed during work with the patient (65%), mentally exhausted (43%), physically exhausted (34%), tired (20%), valued (20%), satisfied with life (18%), burned out (10%) %), frustrated (8%). Only 7% of respondents can talk about their feelings, the remaining respondents are afraid of the teacher's poor opinion (87%) and the therapeutic team (90%). 40% of respondents would definitely go to work abroad. Conclusions: The most common causes of occupational stress are the responsibility for human life and the death of the patient. The respondents rarely seek support among teachers of the profession.